The effect of providing information about the patient's condition on the anxiety level of the family members of hospitalized patients with traumatic brain injury - Maryam Jabbarpour; Fatemeh Abdoli; Majid Kazemi (Tehran University of Medical Sciences, 2018)
Background & Aim: Anxiety is one of the most common psychiatric disorders in the family of patients with traumatic brain injury. This study aimed to determine the effect of providing information about the patient's condition on the anxiety level of the family members of hospitalized patients with traumatic brain injury. Methods & Materials: This quasi-experimental study was conducted on 90 family members of traumatic brain injury patients admitted to Shahid Bahonar hospital in Kerman in 2016. The participants were selected by the consecutive sampling method and were assigned to intervention and control groups. In the intervention, the participants were informed by the nurse about changes in the patient's condition during the first three days of admission to intensive care unit. During this period, the control received routine care. Data collection tool was the Spielberger anxiety inventory. Independent and paired t-test were used to compare the mean scores of anxiety using the SPSS software version 16. Results: There was no statistically significant difference in the mean scores of overt, covert and general anxiety between the two groups before the intervention (P>0.05). However, after the intervention in the experimental group, the mean scores of overt anxiety (45.51±7.26), covert anxiety (45.42±6.51) and general anxiety (90.93±12.72) decreased (P<0.05) compared to the mean scores of overt anxiety (49.22±9.42), covert anxiety (49.02±9.15) and general anxiety (98.24±17.67) in the control group. Conclusion: Providing planned information on changes in the condition of hospitalized patients with traumatic brain injury can reduce the anxiety of family members of these patients. Clinical trial registry: IRCT20180206038642N2